Effect of Tibial Malrotation on Anterior and Posterior Cruciate Ligaments in Bicruciate-Retaining Total Knee Arthroplasty - Sa’audi, Muhammad Saakeereen; Abdullah, Abdul Halim; Shuib, Solehuddin; Mat Raffei, Muhammad Azim; Mohd Miswan, Mohd Fairudz; Mohd Anuar, Mohd Afzan (Makara Journal of Technology, 2024)
Osteoarthritis (OA) is a musculoskeletal disorder specified as a joint disease that affects mostly human joints worldwide. Total knee arthroplasty (TKA) is performed to restore the affected joint and relieve the symptoms. However, tibial malrotation, which is one of the most common errors in TKA, results in poor function of the implant and pain after the procedure. People with OA often experience limited mobility and cannot accomplish daily tasks. Finite element analysis (FEA) has been widely applied to interpret the biomechanical and kinematic force along the joint and investigate the cruciate ligament’s mechanical behavior. Unfortunately, one of the problems in TKA implants is their malalignment affecting tibial rotation. This study employs FEA to investigate the relationship between tibial malrotation and the consequent displacements and forces in the anterior cruciate ligament (ACL) and posterior cruciate ligament (PCL). A subject-specific knee model is used to study the effects of ligament model complexity and simulated ligament wrapping on knee biomechanics and kinematics. Tibial malrotation had a more considerable effect on ACL than on PCL. In terms of ligament forces, both anterior and posterior PCL bundles generated notably greater forces compared with the ACL bundles, with averages of 26823.92 ± 13.32 N and 2796.49 ± 23.98 N, respectively. The displacement of the PCL bundles was also substantial, equaling 26.37 ± 0.01 mm in the anterior and 18.87 ± 0.08 mm in the posterior. Correct implant alignment is essential to avoid overtensioning of the ligament and offers knee joint ligament balance that can restore native knee kinematics.